The Impact of Digital Technology on the Physical Health of Older Workers: Scoping Review - Spijker, Jeroen Ja; Barlin, Hande; Dritsaki, Melina; Gu, Yang; Klavina, Aija; Yaylagul, Nilufer Korkmaz; Kulla, Gunilla; Mercan, Murat Anil; Orhun, Eda; Sevcikova, Anna; Unim, Brigid; Yildizer, Gunay; et al. (JMIR PUBLICATIONS, INC, 2025)
Background: Digital technologies are increasingly present in workplaces; however, their impact on the physical health of older workers remains unclear. Objective: This scoping review aims to examine and summarize the scientific evidence on how digital technology affects the Methods: Following PRISMA-ScR (Preferred Reporting Items for Systematic Reviews and Meta-Analysis extension for Scoping Reviews) guidelines, we conducted a scoping review of English-language peer-reviewed studies extracted from MEDLINE, and context (PCC) framework, including studies on workers aged 50 years or older, any form of digital technology (eg, teleworking and the use of digital tools at work), and its impact on physical health (eg, vision loss and musculoskeletal disorders). Studies that focused only on mental health were excluded. A 13-member research team screened studies in 3 stages, namely title and
Keywords: digital tools; digital technology; physical health; mobility; vision loss; musculoskeletal disorders; older workers; older population; Geriatrics & Gerontology; Medical Informatics